Frontiers of Evangelization: Indians in the Sierra Gorda and Chiquitos Missions - Jackson, Robert H. (University of Oklahoma Press, 2017)
Focusing on the Franciscan missions of the Sierra Gorda in Northern New Spain (Mexico) and the Jesuit missions of Chiquitos in what is now Bolivia, Frontiers of Evangelization takes a comparative approach to understanding the experiences of indigenous populations in missions on the frontiers of Spanish America.